(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The leading place in the structure of general pathology in the workers of mining industry, especially underground mines belongs to diseases of cardiovascular system. In terms of prevalence, severity of course, complications, cardiovascular diseases are one of the main causes of disability, disability, premature death of men of working age.